(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Bhagandara (Fistula-In-Ano) is one of the Astamahagadha disease mentioned in Susrutha Samhitha, which is difficult to cure. Fistula-In-Ano is an abnormal communication between two epithelial-lined surfaces in the anorectal region. Various operative procedures (fistulectomy, etc.) often lead to complication ns like recurrence, incontinence of the anal sphincter, and other infections resulting from surgery. The Kshara Sutra is a parasurgical procedure that is found to be more effective in the management of fistulas in ano. The Apamarga Ksharasutra is widely used and is made up of Apamarga Kshara, Snuhi Kshira and Haridra. The preparation process for Apamarga Kshara can be difficult and time-consuming. If we turn to the classics, we find the reference to Vibhithaki, mentioned under Kshara Dravys, which are used to prepare Ksharasutra. Vibhitaki is cost-effective and easily available as it is a big tree. The properties of Vibhitaki are favourable to Kshara qualities The present clinical study deals with the efficacy of Vibhitaki and Apamarga Kshara Sutras in the management of Bhagandara.